A retrospective content analysis of the ambulance emergency assistant refresher course outcomes as covered by free open access medical education (FOAMED) resources - Steyn, Judy (Stellenbosch : Stellenbosch University, 2018)
Thesis (MMed)--Stellenbosch University, 2018.